Hand preference and hand ability : evidence from studies in haptic cognition - Ittyerah, Miriam (Advances in interaction studies, 2013)
This volume adds new dimension and organization to the literature of touch and the hand, covering a diversity of topics surrounding the perception and cognition of touch in relation to the hand. No animal species compare to humans with regard to the haptic (or touch) sense, so unlike visual or auditory cognition, we know little about such haptic cognition. We do know that motor skills play a major role in haptics, but senses like vision do not determine hand preference or hand ability. It seems also that the potential ability to perform a task may be present in both hands and evidence indicate.